Evaluating the Effectiveness of Positive Career Counseling on Career Decision-Making and Future Orientation - Maisarah, Syarifah; Chen, Mei-Ling (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to evaluate the effectiveness of Positive Career Counseling on career decision-making and future orientation among young adults in Taiwan.Methods and Materials: The study utilized a randomized controlled trial design involving 30 participants from Taiwan, randomly assigned to an experimental group (n = 15) receiving Positive Career Counseling and a control group (n = 15) receiving no intervention. The experimental group participated in nine structured counseling sessions, each lasting 75 to 90 minutes, incorporating strengths-based and future-oriented exercises. Participants completed standardized measures, including the Career Decision-Making Difficulties Questionnaire (CDDQ) and Future Orientation Scale (FOS), at three time points: pre-test, post-test, and a five-month follow-up. Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc tests with SPSS-27.Findings: Results indicated significant improvements in career decision-making and future orientation within the experimental group. Repeated measures ANOVA demonstrated significant time × group interactions for career decision-making (F(2,56) = 16.21, p < .001, η² = .373) and future orientation (F(2,56) = 19.11, p < .001, η² = .405). Bonferroni post-hoc analyses showed meaningful enhancements from pre-test to post-test for both variables (career decision-making mean difference = -14.40, p < .001; future orientation mean difference = -5.73, p < .001). Improvements were sustained at the five-month follow-up, while the control group exhibited no significant changes.Conclusion: These results support the effectiveness of integrating positive psychology and structured future-oriented exercises into career interventions, emphasizing their potential for long-term impact. Such interventions should be adapted for broader populations to enhance career preparedness and psychological resilience in culturally diverse contexts.